Learning Fatigue in Online Education: Cognitive Burnout in the Digital Learning Era - Risza Presty Rumani (Journal of Pedagogi, 2026)
This study examines learning fatigue in online education, a growing issue in the digital era characterized by cognitive overload, Zoom fatigue, and decreased learning performance. As online learning becomes more prevalent, understanding the mechanisms and contributing factors of fatigue is essential for improving instructional effectiveness. This research employs a qualitative approach using a Systematic Literature Review (SLR), analyzing recent peer-reviewed journal articles from databases such as Scopus, Web of Science, and Google Scholar. Data were collected through a structured screening process based on relevance and quality, and analyzed using thematic and content analysis to identify key patterns related to cognitive, technological, pedagogical, and psychosocial dimensions. The findings reveal that learning fatigue is primarily driven by excessive cognitive load, prolonged videoconferencing demands, poor instructional design, and emotional stress. These factors negatively affect attention, motivation, and academic performance. However, mitigation strategies such as optimizing video settings, implementing active learning approaches, balancing cognitive load, supporting self-regulated learning, and fostering social-emotional support can effectively reduce fatigue. The study concludes that addressing learning fatigue requires a holistic and integrated instructional design that aligns cognitive, technological, pedagogical, and psychosocial aspects to create sustainable and engaging online learning environments.